Adaptive Capacity of Fishermen in Facing Tidal Floods with Vulnerability to Viability (V2V) Approach - SBM, Nugroho; Kumar Nayak, Prateep; Susilowati, Indah; Nur Furoida, Aini; Suciati, Ika; Nur Khasanah, Siti; Pratama Putra, Tedy (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2024)
Tambakrejo’s small-scale fishing households have low socio-economic capabilities and must face the problem of tidal flooding. Therefore, this research has the following objectives: 1) To identify the vulnerability of fishing households in Tambakrejo Fishermen Village to social-ecological changes due to tidal flooding. 2) To investigate the adaptive responses of fishermen households in facing socio-ecological changes due to tidal flooding. This research uses primary data by using semi-structured interviews. The number of respondents in the study was 60, determined by the snowball sampling technique. The data were analyzed using descriptive statistical methods. The results of the research show that the community is vulnerable to both natural and institutional aspects. Adaptive responses shape community resilience through increased collaboration capacity and community learning capacity. This research contributes to the government's ability to distribute assistance to the community, especially fishing households affected by tidal flooding.